Modernization of Woven Purun In Various Designs as An Effort To Introduce Local Wisdom of Ngaju Dayak Community - Tanduh, Yusintha; Rahmawati, Reni; Madiyawati, Milad (Green Publisher Indonesia, 2023)
Local wisdom is the noble values that apply in the living system of the community, including protecting and managing the environment sustainably, so local wisdom is a view of life and science as well as various life strategies in the form of activities carried out by local communities in answering various problems in meeting their needs (Law No. 32/2009). Activities or habits that are inherited and owned by a certain member of society, affect many aspects of life, including religion, customs, politics, language, clothing, buildings, to works of art. The purun products produced by partners have relatively little change because the products produced are limited and there are not many options, so they are only used by certain circles and for limited occasions. This product requires breakthrough ideas, both in terms of design/model, and user designation, so that the existence and sustainability of its production can continue to be improved, The purpose of this activity is to provide assistance for community entrepreneurs as business partners by offering solutions / providing insights and encouraging craftsmen to be able to further develop new ideas and breakthroughs in making designs / models in order to produce more modern products according to the tastes of today's consumers